The Sea Wall and the Kampung - Roi Salgueiro Barrio; Sasha McKinlay (Footprint)
We propose that architectural responses to planetary environmental challenges are a crucial domain for cosmotechnical action. We explore the possibilities of cosmotechnical design by analysing two contrasting responses to the effects of anthropogenic climate change in Jakarta: defensive sea-wall construction and adaptive community action. Jakarta is an essential case for exploring cosmotechnics: a world city at the forefront of planetary environmental challenges, and a capital with a conflicted urban history, deeply shaped by colonisation and by its immersion in global circuits of capital and trade.